How much parking space is needed for park and ride facilities to support sustainable infrastructure - Agustin, Imma Widyawati; Dwi Ari, Ismu Rini; Waloejo, Budi Sugiarto; Hariyani, Septiana; Irawati, Sara (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2023)
Park and ride (PR)is the right strategy to overcome transportation problems in metropolitan cities with high mobility levels to realize smart mobility. The three main goals of PR are to reduce congestion levels, increase public transportation use, and improve urban space quality. The provision of parking capacity is one of the success factors in the planning of the PR facility. Therefore it is necessary to calculate the parking space requirement in PR. The research was conducted at Sidoarjo Station, the most significant origin station in Sidoarjo Regency, and a recommended PR location. This study aims to calculate parking space requirements and facilities for the existing conditions and projections when PR operates. Data were collected through primary surveys in the form of observations on parking characteristics at Sidoarjo Station and secondary surveys in literature studies. The results of the study indicate that the existing condition of the parking facility at Sidoarjo Station has exceeded the parking capacity, so to accommodate the need for parking space, it is necessary to increase the parking area of 96 m2 in the existing condition up to 413 m2 or 5,923 m2 for the next ten years.JEL Classification L91; O18; R41